Chemical Variability of Moroccan Myrtle Oil. Issue 9 (4th August 2021) - Bakhy, Khadija; Belhachmi, Touria; Benabdelouahab, Tarik; Tomi, Félix; Casanova, Joseph; Paoli, Mathieu
Abstract: Thirty‐three oil samples isolated from aerial parts of Myrtus communis L. harvested in seven localities, from Northern to Central Morocco, have been analyzed by combination of chromatographic and spectroscopic techniques. The 33 compositions have been subjected to statistical analysis, hierarchical cluster analysis (HCA) and principal component analysis (PCA). Two groups have been differentiated on the basis of their myrtenyl acetate and α ‐pinene contents and each one was sub‐divided in two sub‐groups according to the contents of 1, 8‐cineole and linalool. The compositions of our 33 myrtle oil samples may be named as follow by their main components: sub‐group IA (13/33): α ‐pinene/1, 8‐cineole/linalool; sub‐group IB (6/33): 1, 8‐cineole/ α ‐pinene; sub‐group IIA (10/33): 1, 8‐cineole/myrtenyl acetate; sub‐group IIB (4/33): myrtenyl acetate. Abstract :